433 Antibiotic Compliance in Paediatric Appendicectomies: A Two Cycle QIP in a Tertiary Centre. (19th August 2022) - McLean, E; Gupta, T; Little, J; Hallows, R
Abstract: Aim: Acute appendicitis is the most common surgical condition in children in the UK. We did a Quality Improvement Project to determine if our hospital's paediatric appendicitis antibiotic guidelines were being followed. Method: Data was collected retrospectively for all patients admitted with acute appendicitis between 01/05/2021 and 14/09/2021 at a tertiary paediatric centre. The compliance to centre protocol for antibiotic administration was assessed, including cefuroxime dose per kilogram. Following educational intervention, a second cycle of prospective data collection was performed 29/09/2021 to 18/11/2021 to reassess compliance and close the loop. Results: Initial data collection (n=34) showed protocol compliance at 57.6%; where compliance was correct dose, duration, and combination of antibiotics. Notably, we showed 4 patients developed collections despite being on triple antibiotic therapy. Of these 3 were on the lower dose 20mg/kg Cefuroxime regime despite intraoperative findings. Following a Departmental meeting, the protocol standard dose of Cefuroxime was changed to 50mg/kg (max 1.5 grams as per BNF) for all presentations of acute appendicitis. Results were then fed back to the team and changes implemented; including updating the previous flowchart posters found in A&E, theatres, and ward. Second round of data collection (n=12) showed 91.7% compliance with protocol. Of the patients in this time, none developed abdominal collections. Conclusions: This quality improvement project shows significant improvements in outcomes of appendicectomy, as well as improvements in protocol compliance achieved with education and simple interventions. We have shown an increase in compliance